Pengaruh Komposisi Media Tanam dan Interval Penyiraman Terhadap Laju Pertumbuhan Bibit Kopi Robusta - Ismoyojati, Roni; Devi, Devi (Universitas Nusa Bangsa, 2024)
Various mixtures of planting media and watering with predetermined intervals are used to support the growth process of Robusta coffee seedlings in the early stages of plant cultivation. The aim of this research is to determine how various planting media compositions and watering intervals influence the growth rate of Robusta coffee seedlings. This study used a Randomized Block Design (RBD) with three replication blocks and a 3x3 factorial pattern as an experimental design. The two aspects studied were watering interval (I) and plant media (M). The planting media factor (M) consists of three levels: M0 is top soil media, M1 is top soil and 2:1 TKKS media, and M2 is top soil and 2:1 manure media. The watering interval factor (I) has three levels: I0 indicates a one-day watering interval, I1 indicates a two-day watering interval, and I2 indicates a three-day watering interval. The variables observed included growth rate, dry weight, number of leaves, root length, and plant height. Based on the research findings, there was no interaction between the combination of watering intervals and planting media treatments. However, at the age of 60 HST, 90 HST, and 120 HST there was a significant difference in the variable of plant height between the treatment intervals of watering once every two days (I1), watering once a day (I0), and watering treatment once every three days (I2). At the age of 60 HST there was also a difference in the variable of root length between the planting media treatments. There was a significant difference between the treatment of watering once a day (I0) and the treatment of watering once every two days (I1) in the variable of dry weight at 120 HST. The results of the slope analysis of the line on the logistic pattern growth curve in all treatments showed no significant difference and interaction between the combinations of treatments tested on the variables of plant height and root length. Berbagai campuran media tanam dan pemberian air dengan interval tertentu diuji untuk mendukung proses pembibitan kopi robusta. Tujuan penelitian ini adalah untuk mengetahui bagaimana laju pertumbuhan bibit kopi Robusta dipengaruhi oleh berbagai komposisi media tanam dan interval penyiraman. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) dengan tiga blok ulangan dan pola faktorial 3x3 sebagai rancangan percobaan. Dua faktor yang diteliti adalah interval penyiraman (I) dan media tanaman (M). Faktor media tanam (M) terdiri dari tiga taraf: M0 adalah media top soil, M1 adalah top soil dan media TKKS 2:1, dan M2 adalah top soil dan media pupuk kandang 2:1. Selain itu, Faktor interval penyiraman (I) yang diuji mencakup tiga taraf: I0 menunjukkan interval penyiraman satu hari, I1 menunjukkan interval penyiraman dua hari, dan I2 menunjukkan interval penyiraman tiga hari. Variabel yang diamati meliputi laju pertumbuhan, berat kering, jumlah daun, panjang akar, dan tinggi tanaman. Berdasarkan temuan penelitian, tidak terdapat interaksi antara kombinasi interval penyiraman dan perlakuan media tanam. Namun pada umur 60 HST, 90 HST, dan 120 HST terdapat perbedaan nyata variabel tinggi tanaman antara interval perlakuan penyiraman dua hari sekali (I1), penyiraman sehari sekali (I0), dan perlakuan penyiraman tiga hari sekali (I2). Pada umur 60 HST juga terdapat perbedaan variabel panjang akar antar perlakuan media tanam. Terdapat perbedaan nyata antara perlakuan penyiraman satu kali sehari (I0) dengan perlakuan penyiraman dua hari sekali (I1) pada variabel berat kering 120 HST. Hasil analisis kemiringan garis pada kurva pertumbuhan pola logistik di semua perlakuan menunjukkan tidak ada perbedaan nyata dan interaksi antar kombinasi perlakuan yang diujicobakan pada variabel tinggi tanaman dan panjang akar.